Re-shaping Learning Processes in Vocational Higher Education: a Study on Professional Competences in PBL Methodologies - Pinheiro, Margarida M. (2012)
The main objective of the present work is to analyze and interpret the way changes promoted by PBL methodologies (either as project-based learning or problem-based learning) produce implications for the learning processes in vocational higher education. Path analyses were carried out to evaluate possible changes to the graduates’ profile. The first path analysis investigates if there is any kind of change at the level of how students access and produce knowledge. The second path analysis assesses to what extent PBL contributes to a more professionalized profile. As the main contributions of this study, we highlight: there seems that the transference of previous knowledge to new situations enables integration and consolidation of learning, with a particular magnitude in the increment of competences; PBL methodologies seem to add more value essentially at the beginning of the graduates’ professional career; and there are differences in perception of the type of competencies truly valued by employers